Postbiotics Derived from Lactic Acid Bacteria Fermentation: Therapeutic Potential in the Treatment of Muscular Complications in Inflammatory Bowel Disease - Emili Bruna Toso Bueno; Kimberlly de Oliveira Silva; Maria Eduarda Ferraz Mendes; Lívia Batista de Oliveira; Felipe Prado de Menezes; Anna Cardoso Imperador; Lucimeire Fernandes Correia; Lizziane Kretli Winkelstroter (Fermentation)
Inflammatory bowel disease (IBD) is characterized by chronic inflammation in the gastrointestinal tract, which can result in several muscular complications, including sarcopenia, the loss of muscle mass, and impaired muscle function. Recently, postbiotics derived from lactic bacteria, such as Lactobacillus and Bifidobacterium, have emerged as potential therapeutic modulators for these complications. Postbiotics are bioactive metabolites, such as short-chain fatty acids (SCFAs), antimicrobial peptides, and other compounds produced by microorganisms during fermentation, which have anti-inflammatory, antioxidant, and metabolic regulatory effects. These metabolites are important due to their potential to positively influence muscle health in patients with IBD, mainly by reducing systemic and local inflammation, improving gut microbiota, and modulating muscle metabolism. Studies suggest that these postbiotics may help minimize muscle degradation and promote muscle tissue regeneration, assisting in the prevention or management of IBD-associated sarcopenia. Despite the promising results, challenges remain, such as variability in postbiotic production and the need for further clinical studies to establish clear therapeutic guidelines. This review article explores the mechanisms of action of postbiotics derived from lactic acid bacteria and their potential applications in the treatment of muscle complications in patients with IBD, highlighting future therapeutic perspectives.